2018
DOI: 10.1001/jamapediatrics.2018.1208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen vs Room Air on Intrauterine Fetal Resuscitation

Abstract: IMPORTANCE Two-thirds of women in labor receive supplemental oxygen to reverse perceived fetal hypoxemia and prevent acidemia. Oxygen is routinely administered for category II fetal heart tracings, a class of fetal tracing used to designate intermediate risk for acidemia. This liberal use of oxygen may not be beneficial, particularly because neonatal hyperoxygenation is harmful. OBJECTIVE To test the hypothesis that room air is noninferior to oxygen in improving fetal metabolic status among patients with categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 34 publications
1
52
0
1
Order By: Relevance
“…Our trial randomized 443 normal women and found there were no significant differences between 2 L/min O 2 group and room air group in the abnormal umbilical cord arterial pH values, and found in 217 non-random samples maternal O 2 exposure at super-physiological levels (median arterial blood PO 2 150 mmHg) cannot increase the umbilical cord venous PO 2 (30.2 versus 28.3 mmHg) [ 11 ]. Raghuraman et al [ 24 ] randomized 114 women with nonreassuring FHR tracings and found there were no significant differences between 10 L/min O 2 group and room air group in the abnormal umbilical cord arterial pH and lactate values, and they even found long durations of O 2 exposure were associated with lower in the UvPO 2 (32.5 versus 25.5 mmHg). Thorp et al [ 25 ] randomized 86 normal women and found maternal 10 L/min O 2 exposure were associated with more umbilical cord arterial pH < 7.2 events (9/41 versus 2/44), and found this O 2 exposure cannot increase the in the UvPO 2 (31.2 versus 29.7 mmHg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our trial randomized 443 normal women and found there were no significant differences between 2 L/min O 2 group and room air group in the abnormal umbilical cord arterial pH values, and found in 217 non-random samples maternal O 2 exposure at super-physiological levels (median arterial blood PO 2 150 mmHg) cannot increase the umbilical cord venous PO 2 (30.2 versus 28.3 mmHg) [ 11 ]. Raghuraman et al [ 24 ] randomized 114 women with nonreassuring FHR tracings and found there were no significant differences between 10 L/min O 2 group and room air group in the abnormal umbilical cord arterial pH and lactate values, and they even found long durations of O 2 exposure were associated with lower in the UvPO 2 (32.5 versus 25.5 mmHg). Thorp et al [ 25 ] randomized 86 normal women and found maternal 10 L/min O 2 exposure were associated with more umbilical cord arterial pH < 7.2 events (9/41 versus 2/44), and found this O 2 exposure cannot increase the in the UvPO 2 (31.2 versus 29.7 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not conflict with previous studies. In Raghuraman et al [ 24 ] and Thorp et al [ 25 ] trials, the O 2 flow rate was 10 L/min and the fraction of inspired O 2 (FIO 2 ) was about 60–80%, Thorp et al [ 25 ] showed high level O 2 exposure had no effect on UvPO 2, and Raghuraman et al [ 24 ] even showed longer high level O 2 exposure was associated with lower UvPO 2 . The effects of super-physiological O 2 induced vasoconstriction would reduce blood perfusion of tissue to a greater extent than the little maternal arterial O 2 content rise [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five total articles were included in the systematic review and meta-analysis. [15][16][17][18][19] The search process according to the PRISMA statement is shown in Figure 1.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Characteristics of the five included studies in the meta-analysis are included in Table 1. [15][16][17][18][19] Two studies administered oxygen for NRFHM, 17,18 two administered oxygen prophylactically during the 2 nd stage, 15,19 and one administered oxygen prophylactically for at least 30 minutes before delivery. 16 Two studies administered oxygen at 2L/min 15,16 while three administered oxygen at10L/min.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation